Financial intermediaries, financial stability, and monetary policy - Tobias Adrian; Hyun Song Shin (Federal Reserve Bank of New York, 2008)
In a market-based financial system, banking and capital market developments are inseparable. We document evidence that balance sheets of market-based financial intermediaries provide a window on the transmission of monetary policy through capital market conditions. Short-term interest rates are determinants of the cost of leverage and are found to be important in influencing the size of financial intermediary balance sheets. However, except for periods of crises, higher balance-sheet growth tends to be followed by lower interest rates, and slower balance-sheet growth is followed by higher interest rates. This suggests that consideration might be given to a monetary policy that anticipates the potential disorderly unwinding of leverage. In this sense, monetary policy and financial stability policies are closely linked.
Keywords: E50; G20; 330; Monetary policy; financial stability; financial intermediation; security brokers and dealers; commercial banks; Geldpolitik; Transmissionsmechanismus; Finanzmarkt; Finanzintermediär; Finanzsektor; USA